1995
DOI: 10.1128/iai.63.12.4642-4652.1995
|View full text |Cite
|
Sign up to set email alerts
|

Human antibody responses to meningococcal outer membrane antigens after three doses of the Norwegian group B meningococcal vaccine

Abstract: The antibody kinetics in sera from 27 adults after three doses of the Norwegian group B meningococcal outer membrane vesicle (OMV) vaccine was studied. The vaccinees received the third dose 4 to 5 years after the first two. Antibody responses against outer membrane proteins (OMPs) and lipopolysaccharides were studied by enzyme-linked immunosorbent assay and immunoblotting and with serum bactericidal assays (SBA) with three variants of the vaccine strain, 44/76. Six weeks after the second injection, the geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
100
2
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(118 citation statements)
references
References 56 publications
14
100
2
2
Order By: Relevance
“…These data suggest that PorA treatment is likely to induce a Th2-mediated immune response that is necessary for generating humoral antibody responses required for protective immunity against meningococci. This conclusion is consistent with reports of high levels of antibody to PorA protein(s) detected in individuals following colonization with meningococci (Jones et al, 1998;Williams et al, 2003), invasive disease (Guttormsen et al, 1994;Idanpaan-Heikkila et al, 1995) or vaccination with several different OM vesicle vaccines (Rosenqvist et al, 1995;Peeters et al, 1996;van der Voort et al, 1996;de Kleijn et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…These data suggest that PorA treatment is likely to induce a Th2-mediated immune response that is necessary for generating humoral antibody responses required for protective immunity against meningococci. This conclusion is consistent with reports of high levels of antibody to PorA protein(s) detected in individuals following colonization with meningococci (Jones et al, 1998;Williams et al, 2003), invasive disease (Guttormsen et al, 1994;Idanpaan-Heikkila et al, 1995) or vaccination with several different OM vesicle vaccines (Rosenqvist et al, 1995;Peeters et al, 1996;van der Voort et al, 1996;de Kleijn et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…If Opa does indeed downregulate immune responses in vivo, the deletion of Opa from potential vaccine preparations could improve the immunogenicity of OMVs. Previous clinical trials of OMV vaccines, which contained variable amounts of Opa, have already demonstrated that these vaccines are immunogenic, and that most of the antibody response is directed against PorA (Bjune et al, 1991;Sierra et al, 1991;Rosenqvist et al, 1995;Milagres et al, 1998;Oster et al, 2005Oster et al, , 2007Martin et al, 2006). There is significant variation in anti-Opa antibody responses, both between studies and among individuals within studies (Poolman et al, 1983;Wedege & Froholm, 1986;Mandrell & Zollinger, 1989).…”
Section: T Lymphocytesmentioning
confidence: 99%
“…Because PspA is an antigenically variable protein [17], the epitope for mAb 180,C-1 was detected in only 19 out of 76 examined S. pneumoniae strains. The negative control mAb 184,F-12 (IgG3) reacts with the P1.16 epitope on meningococcal class 1 protein [18].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%